A composite polyaniline/graphene–coated polyamide6 nanofiber mat for electrochemical applications. (17th July 2019) - Tambakoozadeh, Nooshin; Youssefi, Mostafa; Semnani, Dariush
Abstract : In this study, polyamide6 (PA6) nanofiber mats were fabricated through the electrospinning process. The nanofibers were coated by polyaniline (PANI) using the in situ polymerization of aniline in the presence of graphene oxide. The composite of the PANI/graphene oxide–coated nanofiber mat was treated with hydrazine monohydrate to reduce graphene oxide to graphene, and this was followed by the reoxidation of PANI. Field emission scanning electron microscopy (FESEM), Fourier transform infrared spectroscopy (FTIR), wide angle X‐ray diffraction (WAXD), thermal gravimetric analysis (TGA), tensile strength tests, electrical conductivity measurements, cyclic voltammetry (CV), and charge/discharge measurements were conducted on the composite PA6/graphene nanofiber mats. It was found that the surface of the PA6 nanofibers was coated uniformly with the granular PANI and graphene oxide. Besides, the composite nanofibers showed good tensile and thermal properties. Their electrical conductivity and specific capacitance, when used as a separator in the cell, were 1.02 × 10 −4 S/cm and 423.28 F/g, respectively. Therefore, the composite PANI/reduced graphene oxide–coated PA6 nanofiber mats could be regarded as suitable candidates for application in energy storage devices.